2017
DOI: 10.1016/j.jfma.2016.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of type 1 diabetes mellitus in Taiwanese children aged younger than 6 years: A single-center experience

Abstract: Autoimmune destruction of pancreatic β-cells is an important cause of type 1 diabetes mellitus in Taiwanese children aged younger than 6 years. These patients usually have a low insulin reserve and severe ketoacidosis upon diagnosis. A high index of suspicion in the presence of classic symptoms of diabetes in young children is important to prevent complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 28 publications
4
23
0
1
Order By: Relevance
“…We also observed lower rates of PREM in children and adolescents who had DKA at T1D diagnosis, which corroborate previous studies . Indeed, in youth newly diagnosed with T1D, DKA likely reflects a more rapid immune‐mediated destruction of β‐cells, leading to a functional impairment and a more unstable metabolic state . Although our data showed that occurrence of PREM is comparatively more important than DKA at diagnosis for later metabolic control, DKA is a potentially modifiable risk factor.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…We also observed lower rates of PREM in children and adolescents who had DKA at T1D diagnosis, which corroborate previous studies . Indeed, in youth newly diagnosed with T1D, DKA likely reflects a more rapid immune‐mediated destruction of β‐cells, leading to a functional impairment and a more unstable metabolic state . Although our data showed that occurrence of PREM is comparatively more important than DKA at diagnosis for later metabolic control, DKA is a potentially modifiable risk factor.…”
Section: Discussionsupporting
confidence: 90%
“…Rates of PREM obtained from pediatric cohorts have been reported between 35% and 70%, occurring within 3 months after T1D diagnosis . In our study, the percentage of patients in PREM 3 months after new‐onset T1D was approximately 40%, being at the lower end of the spectrum.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…This data has been corroborated in similar Korean hospital‐based studies suggesting increasing LADA prevalence in the Korean population (the prevalence ranging from 3.8% to 5.1%) . In other Asian countries, such as Japan and China, LADA prevalence was also recently reported to be similarly increased . However, there have been few studies reporting the titres of anti‐islet autoantibodies and their prognostic implication .…”
Section: Clinical Heterogeneity Of Diabetes In Asian Patients At Adolsupporting
confidence: 70%